Craniosynostosis - I. T. Jackson; B. Dubin; Ramesh Chandra; D. K. Chabra; Arun Kumar Singh; Pramod Kumar (Indian Journal of Plastic Surgery, 1987)
A 4 year old female child with Graniosynostosis (Grouzon's syndrome) was operated upon on 10.3.87, during the Ist National Workshop on Plastic Surgery at the King George's Medical College, Lucknow, in collaboration with the department of Neuro Surgery. The details of planning, management and the result of treatment in her is being presented.